‘Greening Dharma’: Contemporary Japanese Buddhism and Ecology - Dessì, Ugo (Journal for the study of religion, nature and culture, 2013)
Buddhist environmentalism in Japan during the last few decades manifests through various discussions and forms of activism and is characterized by the use of popular Buddhist ideas, such as aversion to greed, interdependence, and the universality of buddhahood. This movement gained strength after the 2011 Fukushima nuclear power plant accident, when several Buddhist organizations publicly expressed their disapproval of nuclear energy. I argue that rather than a timeless ‘green Dharma’ inherently close to nature, contemporary Japanese Buddhism is a ‘greening Dharma’ that for different reasons is gradually becoming engaged in environmentalism. Although the presence of sincere religious concern and a doctrinal anchorage cannot be overlooked, a crucial role is played by Japanese Buddhism’s need to reassert its presence in the public sphere, and by the involvement of this religious tradition in global dynamics related to residual problems, cultural ?ows, and glocalization.